Densidades de siembra en dos variedades de arroz (Oryza sativa L.) con abono foliar durante la estación húmeda en la localidad de Babahoyo - Gavilánez Jaen, Blanca Herlinda (2020)
The study carried out on planting densities in two varieties of rice (Oryza sativa L.) with foliar fertilizer during the wet season in the town of Babahoyo, has been carried out at the Faculty of Agricultural Sciences of the Technical University of Babahoyo, where it has as objective to determine which treatment is the most effective in the combination of factors A (densities), B (varieties) and C (biostimulants). The experimental design is made up of 12 treatments defined by a factorial arrangement of the densities (55 Kg / ha, 64Kg / ha and 72 Kg / ha), varieties (INIAP 11 and GO-39815) and biostimulants (Crop + plus and KELPAK ), in addition, the methodology used in this research is made up of the inductive, deductive, experimental and observational methods, for the identification of the main findings found in the analysis process, since it is intended to determine the performance of cultivars in three densities of sowing and which is the most effective in the economic field. The investigative tools have been able to determine as a conclusion that the treatments studied only show statistical significance for the characters physiological maturity and panicle length, while the data to evaluate grain yield and days of flowering are significantly different in the variety factor, where it stands out INIAP 11 cultivar, which has higher grain yield, combined with density 2 (64 Kg / ha) and KELPAK biostimulant, with an average of 4621.74 kg / ha. In addition, planting densities and biostimulant did not have a significant impact on the studied treatments, however, the one that showed the greatest benefit was density 1 (55Kg / ha); As for the economic analysis, the treatment that reports profits, but of greater benefit is number three, which corresponds to the combination (density 1 * INIAP 11 * KELPAK), this treatment has a high grain yield (1478.64 Kg / h).